Collusion for Commission by Omission: The case of Mayors and Regional Presidents - Guimaray Mori, Erick (2015)
The business organization of municipal governments allows these entities to be more efficient when performs its role, management and implementation of goods, resources and services for a given community. However, in recent months we have seen various authorities of the district and regional municipalities make use of the business structure of public agencies they belong to commit crimes against the proper functioning of public administration.